2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610684
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sample Entropy of physiological signals by the norm component matrix algorithm: Application on muscular signals during isometric contraction

Abstract: Sample Entropy (SampEn) is a popular method for assessing the unpredictability of biological signals. Its calculation requires to preliminarily set the tolerance threshold r and the embedding dimension m. Even if most studies select m=2 and r=0.2 times the signal standard deviation, this choice is somewhat arbitrary. Effects of different r and m values on SampEn have been rarely assessed, because of the high computational burden of this task. Recently, however, a fast algorithm for estimating correlation sums … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…These commonly used parameters were typically applied to signals with slower dynamics such as heart rate; hence, some studies have suggested that these parameters are inappropriate for signals with faster dynamics, and proposed to use r values that maximize the ApEn value ( Chen et al, 2005 ; Chon et al, 2009 ). However, this maximum entropy approach was shown to be invalid for SampEn estimates ( Castiglioni et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These commonly used parameters were typically applied to signals with slower dynamics such as heart rate; hence, some studies have suggested that these parameters are inappropriate for signals with faster dynamics, and proposed to use r values that maximize the ApEn value ( Chen et al, 2005 ; Chon et al, 2009 ). However, this maximum entropy approach was shown to be invalid for SampEn estimates ( Castiglioni et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some selection methods for dynamic threshold were proposed to replace the constant r. A typical example for ApEn was from the study of Lu et al, regarding the threshold r from 0.01 to 1.0 times of standard deviation of time series maximizing ApEn as the optimal r [15]. A typical example for SampEn was from the study of Castiglioni et al, estimating SampEn over wide ranges of r (0.01 ≤ r ≤ 5) for determining the optimal r [17]. However, the maximum methods for determining r for both ApEn and SampEn are also based on the Heaviside function, which judges two vectors as either "similar" or "dissimilar", without any intermediate states; this could result in the poor statistical stability for entropy estimates.…”
Section: Discussionmentioning
confidence: 99%
“…So the original suggestion between 0.1 and 0.25 times the SD of the time series for r does not always demonstrate the best results for all data sets and therefore, elaborate methods to choose r have been developed. The parameter r may be chosen based on the minimization of the maximum SampEn relative error and conditional probability [8] or to provide the maximum value of ApEn [15] or SmapEn [16,17]. However, our recent study suggested that the maximum value method may not be appropriate for analyzing the nonlinear cardiovascular signals and is only appropriate for known random time series [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…SampEn requires the a priori definition of the same parameters listed for ApEn - N, m and r – and those are typically coincident with the ones used for ApEn (i.e., m = 2, r = 0.2). However, even though some authors consider the same criteria can be used for both SampEn and ApEn [ 49 ], other publications suggest that they should be explored independently since algorithms proposed for the choice of r in ApEn are not applicable for SampEn [ 50 ]. Moreover, appropriate values for m and r depend of the type of signal under analysis [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…SampEn overcomes the bias problem detected in ApEn as well as its inconsistencies, such that if SampEn of one signal (x 1 ) is higher than the value obtained with another signal (x 2 ) for a pair of m and r values, a new m-r pair would still provide higher SampEn values for the signal x 1 [ 51 ]. Nonetheless, Castiglioni et al [ 50 ] detected inconsistencies in SampEn calculations when studying mechanomyographic signals for certain m values, and Yentes et al [ 28 ] published similar findings for some r choices, suggesting that under certain conditions SampEn can also be affected by inconsistencies.…”
Section: Methodsmentioning
confidence: 99%